Democracy and schooling: The paradox of co-operative schools in a neoliberal age?. Issue 6 (28th October 2022) - Woodin, Tom; Gristy, Cath
Abstract: From the first co-operative trust school at Reddish Vale in Manchester in 2006, the following decade would witness a remarkable growth of 'co-operative schools' in England, which at one point numbered over 850. This paper outlines the key development of democratic education by the co-operative schools network. It explains the approach to democracy and explores the way values were put into practice. At the heart of co-operativism lay a tension between engaging with technical everyday reforms and utopian transformative visions of an educational future. A new arena of debate and practice was established with considerable importance for our understanding of democratic education within the mainstream.